2019
DOI: 10.3390/s19092183
|View full text |Cite
|
Sign up to set email alerts
|

The Validity of a Mixed Reality-Based Automated Functional Mobility Assessment

Abstract: Functional mobility assessments (i.e., Timed Up and Go) are commonly used clinical tools for mobility and fall risk screening in older adults. In this work, we proposed a new Mixed Reality (MR)-based assessment that utilized a Microsoft HoloLensTM headset to automatically lead and track the performance of functional mobility tests, and subsequently evaluated its validity in comparison with reference inertial sensors. Twenty-two healthy adults (10 older and 12 young adults) participated in this study. An automa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Face validity can also be demonstrated by comparing groups that are known to walk differently (also known as known-groups validity). Sun et al [3] already evaluated the discriminative ability of functional mobility assessment outcomes derived from HoloLens 1 data. However, no significant differences were found between healthy young and older adults, probably because their walking ability was not too dissimilar for the assessed tasks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Face validity can also be demonstrated by comparing groups that are known to walk differently (also known as known-groups validity). Sun et al [3] already evaluated the discriminative ability of functional mobility assessment outcomes derived from HoloLens 1 data. However, no significant differences were found between healthy young and older adults, probably because their walking ability was not too dissimilar for the assessed tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Mixed-reality headsets, such as Microsoft's HoloLens (Microsoft Corporation, Redmond, WA, USA; Figure 1A), are untethered and consist of a non-occluding holographic display unit through which 3D holograms can be anchored in the wearer's environment. Mixed-reality has been studied in various applied contexts, including, but not limited to, assistance during surgical interventions (e.g., [1,2]), remote medical assessments or support (e.g., [3,4]), and walking-ability assessments with holographic obstacle avoidance [5]. To ensure that holographic content realistically blends with the real environment, the headset must sense its position and orientation with respect to the surrounding, which requires many sensors, including an inertial measurement unit, four 'environment-understanding' cameras, a depth camera (see for example Hübner et al [6] for a HoloLens sensor evaluation study) and a set of algorithms (Simultaneous Localization and Mapping, SLAM) to compute the position and orientation of the headset with respect to its surrounding, while at the same time mapping the structure of that environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sun et al have developed two AR-based automated functional mobility test using Hololens AR HMD: Sit To Stand (STS) and Time Up and Go (TUG). In comparison with reference inertial sensor (Opal, APDM), vertical kinematic data (displacement, velocity and acceleration) shown a bias less than 0.02 s for STS and 0.13 s for TUG, with range of error within ±0.8 s. Correlation coefficient for kinematic measurement agreement between Hololens and reference sensors were from 0.74 to 0.99 [ 47 ]. We obtained similar results with HoloStep for kinematic measurement.…”
Section: Discussionmentioning
confidence: 99%
“…However, AR motion sensors must be rigorously vetted to establish the validity and reliability of the data prior to clinical integration. Recently, the first generation of head-mounted AR system, HoloLens 1 (HL1) (Microsoft Corporation, Redmond, CA) was validated for the assessment of gait and physical mobility [16,17]. Overall, the studies revealed good agreement between the HL1 outcomes for measures of accuracy in step detection and overall task time.…”
Section: Introductionmentioning
confidence: 99%